Improved corrosion resistance of mild steel against acid activation: Impact of novel Elaeis guineensis and silver nanoparticles - Ali Asaad, M.; Sarbini, N.; Sulaiman, A.; Ismail, Mohamed; Huseien, G.; Abdul Majid, Z.; Bothi Raja, P. (Elsevier, 2018)
© 2018 Influence of novel green Elaeis guineensis (EG) and silver nanoparticles (AgNPs) on the improved corrosion resistance of mild steel against acute acid attack is reported. Such EG/AgNPs were synthesized from palm oil leaf extracts and used as inhibitor with varying contents to inspect the feasibility of modifying the acid (1 M HCl(aq)) mediated anti-corrosion behaviour of mild steel. The structural and morphological properties of the extracted EG/AgNPs inhibitor (in powder form) were determined using TEM, XRD, and EDX analyses. Furthermore, the acid solution exposed mild steel specimens were characterized via FESEM, EDX, AFM, XRD, weight loss, polarization and electrochemical impedance measurements. Mild steel surface was found to adsorb the EG/AgNPs and formed a protective film advantageous for inhibiting the acid attack. Steel specimen incorporated with 10% (v/v) of EG/AgNPs inhibitor revealed maximum inhibition efficiency of 94.1%.